Pain in the bipolar disorder: prevalence, characteristics and relationship with suicide risk - Ana Carolina Ferreira Rosa; Eliseth Ribeiro Leão (Universidade de São Paulo, 2021)
Objective: to know the prevalence and characteristics of pain, to verify how pain management has been carried out by the health services, and to correlate suicide risk with pain intensity in patients with bipolar disorder. Method: an observational study with a quantitative approach. The study included people with bipolar disorder assessed by the McGill-Reduced Pain Questionnaire, Body Diagram, Visual Numerical Scale, and the Suicidal Ideation Scale (Beck). Results: the sample of 60 participants was mainly composed of women with a mean age of 40 years old and a mean psychiatric treatment time of approximately 13 years. Of these, 83% reported feeling pain at the time of the interview. Half of the participants indicated that pain interferes with routine and 80% did not receive care in health institutions. The main descriptors that qualify the painful experience were as follows: painful, heavy and sensitive for the sensory descriptors, tiring and punishing in the affective category. Suicide attempt was reported by 57% of the participants. There was a correlation between suicide risk and pain intensity. Conclusion: pain presented a high prevalence. Suicide risk was identified in more than half of the participants. Pain intensity showed a significant correlation with suicide risk.